Transcending Boundaries of Rationality and Spirituality: Ibn ‘Arabi’s Holistic Vision in Islamic Legal Interpretation - Junaidi, Ahmad; Waeno, Muhammadaree; Amal, M. Khusna (Teosofi: Jurnal Tasawuf dan Pemikiran Islam, 2024)
The higher objectives of the Sharia provide a legal framework within Islamic law to guide independent reasoning in interpreting legal issues based on rational principles. However, knowledge can also be obtained through unveiling. Ibn ‘Arabi argued that intellectual activities without spiritual experience are like spiritual perceptions without intellectual support. His analysis involved a systematic and rigorous approach to understanding and interpreting Islamic law through philosophical, linguistic, and historical contextualization. Ibn ‘Arabi relied on inner knowledge when examining legal issues and performed a type of spiritual ijtihād, but he did not disregard the role of traditional scholarship in Islamic jurisprudence. This balanced approach highlights the integration of rational and spiritual dimensions in legal reasoning, emphasizing the importance of both intellectual and spiritual insights in the interpretation of Islamic law. By combining these elements, Ibn ‘Arabi’s methodology offers a comprehensive understanding of legal issues, ensuring that interpretations are both deeply rooted in traditional scholarship and enriched by personal spiritual experiences. This dual approach underscores the dynamic and multifaceted nature of Islamic jurisprudence, where rational analysis and spiritual insight work together to achieve a holistic understanding of the law.